2001
DOI: 10.1021/np0102354
|View full text |Cite
|
Sign up to set email alerts
|

Rocaglamides, Glycosides, and Putrescine Bisamides from Aglaia dasyclada

Abstract: A phytochemical analysis of the leaves of Aglaia dasyclada collected in Yunnan Province (People's Republic of China) yielded five cyclopentabenzofurans (1-5) of the rocaglamide family that are common secondary metabolites of Aglaia species as well as four biogenetically related compounds of the aglain (7), aglaforbesin (8) and forbaglin (9, 10) types. In addition, the cinnamic acid amide dasyclamide (6), which is a putative biogenetic precursor of these compounds (7-10), was isolated. The structures of the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Two methoxyl groups, three aromatic rings, one phenyl group, one parasubstituted phenyl, and one aromatic ring with meta positions unsubstituted were deduced from the 1 H NMR spectrum ( Table 1). Analysis of the 1 H and 13 C NMR spectra of 2 indicated a similar skeleton to those of aglains [6]. However, the down-field carbon signal (d C 76.0, s) indicated that 2 had a new 2-hydroxy-2-methylbutyryl group, similar to aglaxiflorins A -D [10].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Two methoxyl groups, three aromatic rings, one phenyl group, one parasubstituted phenyl, and one aromatic ring with meta positions unsubstituted were deduced from the 1 H NMR spectrum ( Table 1). Analysis of the 1 H and 13 C NMR spectra of 2 indicated a similar skeleton to those of aglains [6]. However, the down-field carbon signal (d C 76.0, s) indicated that 2 had a new 2-hydroxy-2-methylbutyryl group, similar to aglaxiflorins A -D [10].…”
Section: Resultsmentioning
confidence: 93%
“…Its UV spectrum indicated absorptions at 208 and 278 nm, consistent with the characteristic of lignans. In addition, the 1 H NMR spectrum of 1 showed four methoxyl groups, one phenyl group, one trisubstituted phenyl group, and one oxygenated benzene group with two meta protons, indicating typical signals of rocaglamides or aglains [6]. Its characteristic quaternary signals of d C 101.5 (s, C-3a) and 93.0 (s, C-8b) in the 13 C NMR spectrum (Table 1) further suggested it was a rocaglamide analog rather than aglains [7].…”
Section: Resultsmentioning
confidence: 99%
“…1) As part of our continuing search for bioactive constituents from Thai medicinal plants, [2][3][4] separate hexane and dichloromethane soluble extracts of the fruits of A. cucullata were found to exhibit significant cytotoxic activity when evaluated against a panel of human cell lines. Fractionation of the hexane and dichloromethane extracts led to the isolation of two new naturally occurring cyclopenta [b]benzofuran, 1-O-formylrocagloic acid (1) and 3Ј-hydroxyrocagloic acid (2), along with five known compounds, rocaglaol (3), 5) rocagloic acid (4), 6) 3Ј-hydroxymethylrocaglate (5), 7) 1-Oformylmethyl rocaglate (6), 5) and methylrocaglate (7), 5) from the fruits of A. cucullata. The structures of the known compounds were elucidated by comparison of their physical and spectral data with literature values.…”
mentioning
confidence: 99%
“…10,44 In addition, if there were a C-4 α-oriented phenyl ring, the 6-OCH 3 protons would be shielded from around δ H 3.88 to approximately 3.11. 10,43 In the 1 H NMR spectrum of compound 1, the 6-OCH 3 protons appeared at δ H 3.88, which implied the absence of any shielding effect from the benzene ring, and confirmed the β orientation of the C-4 phenyl group. The observed NOESY cross peaks of H-10/H-3, H-2′(6′) and H-2″(6″), as well as H-3/H-2′(6′) and H-2″(6″), further supported the 3-βH and 4-αH orientation and established the endo relationship between H-10 and H-3 ( Figure 1).…”
Section: Resultsmentioning
confidence: 77%